A 3D process simulation model for wet compression moulding. (June 2021) - Poppe, Christian T.; Krauß, Constantin; Albrecht, Fabian; Kärger, Luise
Abstract: Wet Compression Moulding (WCM) provides large-scale production potential for continuously fibre-reinforced structural components due to simultaneous infiltration and draping during moulding. Due to thickness-dominated infiltration of the laminate, comparatively low cavity pressures are sufficient - a considerable economical advantage. Similar to other Liquid Compression Moulding (LCM) processes, forming and infiltration strongly interact during process. However, the degree of forming is much higher in WCM, which disqualifies a sequential modelling approach. This is demonstrated in this work via experimental characterisation of the interaction between compaction and permeability of a woven fabric and by trials with a transparent double dome geometry, which facilitates an in situ visualization of fluid progression during moulding. In this light, and in contrast to existing form filling approaches, a forming-inspired, three-dimensional process simulation approach is presented containing two fully-coupled macroscopic forming and fluid-submodels. The combined model is successfully benchmarked using experimental double dome trials with transparent tooling.